On the Splitting Dynamics of Meetup Social Groups - Bhowmick, Ayan Kumar; Pramanik, Soumajit; Pathak, Sayan; Mitra, Bivas (Proceedings of the International AAAI Conference on Web and Social Media, 2020)
Groups in online social networks witness continuous evolution by loss of existing members and gain of new members. In this paper, we present a study of group split in Meetup, where a major fraction of members leave the existing group together and join a newly formed group. We identify pivotal group members, called splitters, playing key roles in group split by influencing the existing members to leave the group. We provide an in-depth analysis of the empirical data to reveal key motivating factors leading to a group split and its subsequent impact. Finally, we develop a prediction model for early detection of splitters, as well as the group members likely to be influenced by the splitter to leave the group.